2008
DOI: 10.1007/s10552-008-9151-8
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in a cohort of patients with systemic lupus erythematosus (SLE) in California

Abstract: Objective-We conducted a retrospective cohort study to examine cancer risk in a large cohort of systemic lupus erythematosus (SLE) patients in California.Methods-The cohort consisted of individuals with SLE derived from statewide patient discharge data during the period 1991-2002. SLE patients were followed using cancer registry data to examine patterns of cancer development. Standardized incidence ratios (SlRs) and 95% CI were calculated to compare the observed to expected numbers of cancers based on age-, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
5
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(166 citation statements)
references
References 42 publications
(59 reference statements)
6
153
5
2
Order By: Relevance
“…On the other hand, there is a gradual increase of risk ratios of myeloid malignancies over age in SLE patients and the peak of risk ratio was observed in patients aged more than 70 years. Our findings are different from previous studies by Parikh-Patel et al 12 and Chen et al, 14 showing that the peaks of risk for haematologic malignancies may occur in mid-age and old age groups. Parikh-Patel et al 12 discovered that the risk of non-Hodgkin's lymphoma (NHL) occurred in younger SLE patients and the risks appeared to decrease with age.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is a gradual increase of risk ratios of myeloid malignancies over age in SLE patients and the peak of risk ratio was observed in patients aged more than 70 years. Our findings are different from previous studies by Parikh-Patel et al 12 and Chen et al, 14 showing that the peaks of risk for haematologic malignancies may occur in mid-age and old age groups. Parikh-Patel et al 12 discovered that the risk of non-Hodgkin's lymphoma (NHL) occurred in younger SLE patients and the risks appeared to decrease with age.…”
Section: Discussioncontrasting
confidence: 99%
“…[1][2][3][4][5] Previous studies have reported higher risks of haematologic malignancies in SLE patients; however, there is a limited understanding of the aetiologies, especially age-related factors. [6][7][8][9][10][11][12] The age-risk relationship provides information on the mechanism of carcinogenesis; however, the data for haematologic malignancies and SLE remain very limited. Alarcon et al reported the increased risks of malignancies in younger SLE patients and attributed them to more aggressive treatment with immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior studies did not find the increased risk of prostate cancer in patients with SLE [5][6][7]18], or even a lower risk [19]. To the best of our knowledge, there was only one earlier paper presented a significantly higher risk.…”
Section: Discussionmentioning
confidence: 80%
“…Patients in the non-RD group who exhibited high CRP levels also displayed poorer overall survival than those with low CRP levels (5-year survival rate: 78.3% vs. 90.0%; P ¼ 0.044; (data not shown). [8][9][10][11] it remains controversial whether RD is a risk factor for solid cancers. In a meta-analysis of 21 publications reported in 2008, RA was identified as a risk factor for lymphoma and lung cancer, but the incidence of colorectal and breast cancers was lower in patients with RA.…”
Section: Resultsmentioning
confidence: 99%